Native whey protein with high levels of leucine results in similar post-exercise muscular anabolic responses as regular whey protein: a randomized controlled trial - Håvard Hamarsland; Anne Lene Nordengen; Sigve Nyvik Aas; Kristin Holte; Ina Garthe; Gøran Paulsen; Matthew Cotter; Elisabet Børsheim; Haakon B. Benestad; Truls Raastad (Taylor & Francis Group, 2017)
Background Protein intake is essential to maximally stimulate muscle protein synthesis, and the amino acid leucine seems to possess a superior effect on muscle protein synthesis compared to other amino acids. Native whey has higher leucine content and thus a potentially greater anabolic effect on muscle than regular whey (WPC-80). This study compared the acute anabolic effects of ingesting 2 × 20 g of native whey protein, WPC-80 or milk protein after a resistance exercise session. Methods A total of 24 young resistance trained men and women took part in this double blind, randomized, partial crossover, controlled study. Participants received either WPC-80 and native whey (n = 10), in a crossover design, or milk (n = 12). Supplements were ingested immediately (20 g) and two hours after (20 g) a bout of heavy-load lower body resistance exercise. Blood samples and muscle biopsies were collected to measure plasma concentrations of amino acids by gas-chromatography mass spectrometry, muscle phosphorylation of p70S6K, 4E-BP1 and eEF-2 by immunoblotting, and mixed muscle protein synthesis by use of [2H5]phenylalanine-infusion, gas-chromatography mass spectrometry and isotope-ratio mass spectrometry. Being the main comparison, differences between native whey and WPC-80 were analysed by a one-way ANOVA and comparisons between the whey supplements and milk were analysed by a two-way ANOVA. Results Native whey increased blood leucine concentrations more than WPC-80 and milk (P < 0.05). Native whey ingestion induced a greater phosphorylation of p70S6K than milk 180 min after exercise (P = 0.03). Muscle protein synthesis rates increased 1-3 h hours after exercise with WPC-80 (0.119%), and 1-5 h after exercise with native whey (0.112%). Muscle protein synthesis rates were higher 1-5 h after exercise with native whey than with milk (0.112% vs. 0.064, P = 0.023). Conclusions Despite higher-magnitude increases in blood leucine concentrations with native whey, it was not superior to WPC-80 concerning effect on muscle protein synthesis and phosphorylation of p70S6K during a 5-h post-exercise period. Native whey increased phosphorylation of p70S6K and muscle protein synthesis rates to a greater extent than milk during the 5-h post exercise period. Trial registration This study was retrospectively registered at clinicaltrials.gov as NCT02968888.